Molecular Structure, Vibrational Spectra, Theoretical NBO and HOMO-LUMO Analysis of Bi-Glycine Hydrobromide by DFT Method - Balamurugan, N.; Charanya, C.; Sampathkrishnan, S. (Asian Journal of Chemistry, 2014)
An organic non linear optical material of bi-glycine hydrobromide was successfully grown by slow evaporation method. The optimized molecular geometry, harmonic vibrational spectra, natural bond orbital (NBO) analysis, highest occupied molecular orbital and lowest un occupied molecular orbital, milliken atomic charge, thermodynamic properties of zero-point vibrational energies, rotational constants, dipole moment, entropies were calculated for the title compound by density functional B3LYP method with 6.31 ++G(d,p) basis set using Gaussion 03 W program program package on a intel core i3/1.6 GHz personal computer. We also recorded the FT-IR, FT Raman spectra of bi-glycine hydrobromide at room temperature.